Autopsy findings of fatal cryptogenic organizing pneumonia - Terada, Tadashi (e-Century Publishing Corporation, 2013)
Autopsy cases of cryptogenic organizing pneumonia (COP) have been rarely reported. A 73-year-old Japanese man consulted to a hospital because of flu-like sickness. He was diagnosed as pneumonia, and treated by antibiotics. He was referred to our hospital for further treatment. Chest X-P showed pneumonia involving the whole lungs. Blood laboratory test showed leukocytosis, increased CRP, and decreased PaO(2). Despite of steroid therapy, he showed a downhill course and died one month after the first manifestation. The clinical diagnosis was acute pneumonia or ARDS. At autopsy, the both lungs were voluminous. The weight of lungs was 1050 g in the left lung and 1300 g in the right lung. The both lungs were entirely affected. The lungs were hard and little air was recognized. Microscopically, almost all alveolar spaces contained Masson’s bodies. Bronchiolitis obliterans was not recognized. The alveolar walls were not affected. The Masson’s bodies showed collagenization with lymphocytic infiltration. Hyalinization of Masson’s bodies with little inflammatory infiltration was frequently seen. Cartilagenous metaplasia and ossification of Masson’s bodies were seen in some places. The pulmonary arteries were affected by fibrosis, and occasionally showed thrombosis. The pathological diagnosis was COP. The heart weighted 500 g, and showed right ventricular hypertrophy (cor pulmonale). Other pathologic changes were pleural effusion (left, 800 ml: right, 1200 ml), acute liver congestion, prostatic hypertrophy, colon adenoma, and hypercellular bone marrow. The cause of death was respiratory failure due to COP and pleural effusion. In conclusion, the author reported an autopsy case of fatal COP.